Rapid green synthesis of silver nanoparticles using leaf extract of ficus auriculata: characterization and antimicrobial studies - GURPREET KOUR; S C SATI; MANISHA SATI (International Journal of Pharma and Bio Sciences, 2017)
Ecofriendly and stable silver nanoparticles have been synthesized using aqueous leaf extract of Ficus auriculata without using any synthetic reagent. In the present study it was observed that silver ions were reduced by leaf extract within 10 minutes leading to formation of silver nanoparticles. The synthesized silver nanoparticles are characterized by UV-Vis spectroscopy, XRD, High resolution scanning electron microscopy (SEM) and High resolution transmission electron microscopy (TEM). UV-Vis analysis of the sample confirmed the formation of silver nanoparticles exhibiting a peak at a wave length of 437nm. HR-TEM showed that the synthesized silver nanoparticle has spherical shape with a mean size ranging from 23nm to 67nm silver nanoparticles showed antimicrobial activity against Bacillus cereus and Klebsiella pneumonia.